2022
DOI: 10.3390/horticulturae8070661
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Different Methods for Pruning Pitaya (Hylocereus undatus)

Abstract: Recently there have been new trends in global consumption toward fresh foods that are sources of healthy bioactive compounds, as is the case with pitaya. However, pitaya cultivation is a relatively recent phenomenon and little is known about its management. The objective of this work is to determine the most appropriate annual fruiting pruning method for pitaya in order to obtain a regular annual yield of quality fruit and an intense shoot renewal that guarantee future production. This study compared the respo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Allahabad Safeda. Arredondo et al, (2022) [5] perceived that with increase in pruning intensity (with full shoot pruning) fruit number is decreased while there was very less or no fruiting during the rainy season. Comparable results were submitted by (Chander et al, 2022) [8] .…”
Section: Fruit Numbermentioning
confidence: 99%
“…Allahabad Safeda. Arredondo et al, (2022) [5] perceived that with increase in pruning intensity (with full shoot pruning) fruit number is decreased while there was very less or no fruiting during the rainy season. Comparable results were submitted by (Chander et al, 2022) [8] .…”
Section: Fruit Numbermentioning
confidence: 99%
“…Pitaya pruning involves trimming back long, broken, tangled, or dead stems once annually in young plants and three times in mature plants [ 23 , 135 ]. A study on H. undatus pruning shows that cane pruning induces maximum flowering and produces new shoots as compared to spur, spur–cane combined, and sanitary pruning [ 136 ]. Another study further reported improved yield characteristics of pitaya with cane pruning, leaving 12 and 15 cladodes per meter on a trellis [ 137 ].…”
Section: Agronomy Cultivation Pests and Diseasesmentioning
confidence: 99%